2019
DOI: 10.3390/su11154028
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for the Adoption of Health-Based Sustainable Dietary Patterns: A Review on Consumer Research of Meat Substitutes

Abstract: This article reviews empirical research on consumers’ adoption of meat substitutes published up to spring 2018. Recent meat substitutes often have sustainable characteristics in line with consumers’ concerns over aspects of healthy food and the environmental impact of food production. However, changing lifestyles with less time for cooking, any transition from a strongly meat-based to a more plant-based diet depends on the successful establishment of convenient meat substitutes. This article reviews the growin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 45 publications
2
56
0
Order By: Relevance
“…According to a recent review of consumer research, Weinrich found that environmental arguments were not the basis for decisions to purchase and consume from this category of plant-based meat substitutes. Taste, appearance and availability were far more important [14]. The number of products available in mainstream supermarkets is five times that of 2015 and now products are often placed in the chilled meat section adjacent to meat, many with a clear window as part of the packaging so the appearance and similarity to meat is in view.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a recent review of consumer research, Weinrich found that environmental arguments were not the basis for decisions to purchase and consume from this category of plant-based meat substitutes. Taste, appearance and availability were far more important [14]. The number of products available in mainstream supermarkets is five times that of 2015 and now products are often placed in the chilled meat section adjacent to meat, many with a clear window as part of the packaging so the appearance and similarity to meat is in view.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing consumption of plant-based foods, and decreasing animal foods, has been described as a health and environmental ‘win-win’ by authors of the EAT Lancet report, which describes targets for a healthy diet and sustainable food production system [13]. Greater knowledge and awareness means sustainability has emerged as a significant focus for food producers and consumers alike, based on three dimensions; ecological, social and economic, and now a fourth dimension focused on health [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implications of such drastic economic transitions should be further explored, especially for the well-being of farmers and farmworkers, who already experience poor mental health outcomes compared to other professions due to a variety of factors including financial stress, pesticide exposure, and climate variabilities (Daghagh et al, 2019). This is especially pertinent given recent media attention (the scientific literature has not caught up yet) to a looming economic and suicide crisis among American farmers considering the persistent agricultural recession, diminished farm income, rapidly increasing debts, and extreme flooding events (Harvie, 2017;Weingarten, 2018;Simpson, 2019). Moreover, if cell-based meat were produced in cities, it could also further perpetuate rural population loss and the associated disintegration of rural economies, which are largely dependent on agriculture (Tuomisto and Teixeira de Mattos, 2011;Johnson and Lichter, 2019;Pender et al, 2019).…”
Section: Socio-economic Implicationsmentioning
confidence: 99%
“…While the relationship between diet and sex/gender, especially in the context of meat consumption, has been the subject of scientific debate for a long time [30][31][32], scientists have only recently begun to empirically study people who exclude meat from their diet, i.e., vegans/vegetarians. The purpose of this review is to raise awareness of the gender differences as regards social perceptions, but also in terms of individual attitudes to vegetarian/vegan diets.…”
Section: Introductionmentioning
confidence: 99%